The Oretical and Experimental Vibrational Spectra of Kyotorphin Dipeptide - Yılmaz, Ayberk; AKYÜZ, SEVİM (Elsevier, 2005)
The vibrational wavenumbers of kyotorphin [l-Tyr1–d-Arg2] analogue (d-KTP) was determined by using theoretical and experimental methods. The optimised structure of kyotorphin was obtained on the basis of parameter set determined for l-tyrosine and d-arginine molecules. After then the vibrational wavenumbers of kyotorphin were calculated by density functional theory (DFT) approximation, using the B3LYP function with 6-31G(d,p) basis set. The vibrational assignment was given by the help of total energy distribution (TED) of the vibrational modes of the d-KTP. The characteristic Fermi doubled of tyrosine was observed at 853 and 828 cm−1 in the Raman spectrum of d-KTP and the intensity ratio (I853/I828) was found to be 1.6, indicating that both phenoxyl proton and oxygen are involved in H-bonding interaction in d-KTP.
Keywords: Ab Initio; Aminoacids; Arginine; Density Functional Theory; IR and Raman Spectra; Kyotorphin; Tyrosine